واقع نظم المعلومات وأثرها في الأداء التجاري للمصرف التجاري السوري من وجهة نظر العاملين في هذا المصرف دراسة ميدانية في فروع المصرف التجاري في محافظة طرطوس - حيدر, عز الدين; وقاف, يوسف (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This research aims to studying the reality of information systems in Syrian Commercial Bank and its branches in Tartous governorate and to studying their impact on improving the commercial performance in these branches.Used data was obtained from a questionnaire designed by the researcher. The search reached many results, the most important of which: - The enhancement of computer information systems at the Commercial Bank positively reflected on commercial performance of this bank. - Computer information systems contribute to enhance the trade performance through the following: Improve the quality of services. Achieve customer satisfaction. Diversification of services. Increase the number of customers. The researcher concluded with a number of recommendations, the most important of which are: - To activate the role of computer information systems in banking, which is of great importance in the good impact on commercial performance of commercial banks. - Conduct periodic studies on computer services provided at banks in order to assess their ability to improve the commercial performance of these banks. تهدف هذه الدراسة إلى التعرف على واقع نظم المعلومات في فروع المصرف التجاري السوري في محافظة طرطوس وأثرها في تحسين الأداء التجاري في تلك الفروع، وذلك من خلال بيانات تم الحصول عليها بواسطة استبانة صممها الباحث. توصل البحث إلى جملة نتائج أهمها: - إن تحسين نظم المعلومات الحاسوبية في المصرف يسهم في تحسين الأداء التجاري لهذا المصرف. - تساهم نظم المعلومات الحاسوبية في تحسين الأداء التجاري من خلال ما يلي: تحسين جودة الخدمات. تحقيق رضى الزبائن. تنويع الخدمات. زيادة عدد الزبائن. وخلص الباحث إلى مجموعة من التوصيات أهمها: - العمل على تفعيل دور نظم المعلومات الحاسوبية في الأعمال المصرفية لما له من أهمية بالغة في التأثير الجيد على الأداء التجاري للمصارف التجارية. - إجراء دراسات دورية عن الخدمات الحاسوبية المقدمة في المصارف بغية تقييم قدرتها على تحسين الأداء التجاري في تلك المصارف.